Detecting novel mutations and combined Klinefelter syndrome in Usher syndrome cases. (3rd June 2019) - Li, Xiaohong; Huang, Shasha; Yuan, Yongyi; Lu, Yu; Zhang, Dejun; Wang, Xiaobin; Yuan, Huijun; Han, Weiju; Dai, Pu
Abstract: Background: Usher syndrome (USH) is an autosomal recessive disease characterized by hearing loss, vision loss, and occasionally vestibular dysfunction. Klinefelter syndrome (KS) is an X chromosome polyploidy characterized by one or more additional X chromosomes in males. To date, there has been no report of USH combined with KS. Objectives: This study examined the causative genes in three Chinese probands with congenital hearing loss. Material and methods: Targeted next-generation sequencing (NGS) was performed to identify mutations in three probands with hearing loss. Low-coverage whole-genome sequencing (WGS) analysis of aneuploidy was used to verify the chromosome aneuploidy. Results: Four novel MYO7A mutations were identified in two USH1 probands who were initially diagnosed with nonsyndromic hearing loss until the onset of vision loss. Another case was initially diagnosed with nonsyndromic hearing loss and USH2 and KS were discovered incidentally after the genetic analysis. Conclusions: Our findings expand the mutation spectrum of MYO7A . This is also the first report of concomitant USH and KS. Genetic testing can help with clinical management, particularly if an unrecognized syndromic disorder is identified before the onset of additional symptoms. A clinical genetic evaluation is recommended as part of the diagnostic work-up in congenital hearing loss.